Analisis Kausalitas Antara Pengeluaran Pemerintah, Konsumsi Rumah Tangga, Dan Pendapatan Asli Daerah Di Provinsi Sumatera Utara - Lubis, Bela Ananda; Samsuddin, M. Afdal (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the causal relationship between Government Expenditure (PP), Household Consumption (KRT), and Local Own-Source Revenue (PAD) in North Sumatra Province during the period 1995–2024. The method used is the Vector Error Correction Model (VECM), selected after a series of stationarity tests, optimal lag determination, stability tests, Granger causality tests, and Johansen cointegration tests. The results show a significant bidirectional causal relationship between PAD and PP, as well as a significant effect of PAD on KRT, but no causal relationship from KRT to other variables. The cointegration test confirms three long-term relationships among the variables, justifying the use of the VECM model. In the long term, PAD plays an important role in adjusting the equilibrium of the regional economic system, while in the short term, changes in PP and PAD significantly affect the dynamics of their respective variables. The impulse response results indicate that PP and KRT are more responsive to shocks in themselves, while PAD acts as the main driver in correcting long-term disequilibrium. These findings emphasize the importance of strengthening PAD and effective management of government expenditure to support sustainable regional economic growth in North Sumatra Province.